Parenting Style on the Civics Learning Outcome - Ketut Ari Yuliani; Desak Putu Parmiti; Gede Wira Bayu (Universitas Pendidikan Ganesha, 2022)
The implementation of learning in the school is pretty good, but learning at home is not optimal because students have less desire to learn independently. Lack of parenting guidance interfered with learning activities. This study aimed to analyze the relationship between parenting styles and learning outcomes of fifth-grade elementary school students in Civics subject. The type of research was ex post facto. The research population was 37 students. Students on the first semester of the fifth-grade elementary school. The method of collecting data was non-test. The questionnaire was used as an instrument to collect the data. The data analysis technique used was descriptive statistical analysis and inferential statistical analysis. The study results were 0.655 > 0.316, so there was a correlation between study habits and the learning outcomes of fifth-grade elementary school students. There was a positive relationship between parenting and learning outcomes. It was concluded that a good parenting style would significantly improve student learning outcomes.